(untitled) (Economics and region, 2024)
The purpose of the study is to identify the features of state regulation of product quality in the context of ensuring safety on the domestic market. It has been proven that the aim of the study is to determine the features of state regulation of product quality in the context of ensuring safety on the domestic market. It is identified that state regulation of product quality directly affects the safety of the domestic market, preventing the influx of substandard goods that could undermine the local industry. The safety aspects of products on the domestic market have been characterized. It is proven that state regulation of product quality in the context of ensuring the safety of the domestic market represents a system of legislative and regulatory measures aimed at establishing and controlling the execution of mandatory standards and requirements for the quality of goods and services offered to consumers. It is determined that regulation is aimed at protecting the life and health of consumers, reducing the risks associated with the use of dangerous goods, ensuring fair trade, and supporting trust in the market, which collectively contributes to the stability and safety of the domestic market. The features of the impact of state regulation on the quality of products sold on the domestic market are highlighted. It is proven that state regulation of product quality also plays a crucial role in protecting domestic industry and jobs. By setting high standards, the state can prevent the flow of cheap and substandard imports, which can undermine the positions of domestic producers who invest in high-quality production. It is determined that state regulation of product quality plays a crucial role in ensuring the safety of the domestic market, offering numerous positive effects that contribute to the overall well-being of consumers and the stability of the economy. State regulation, ensuring compliance of all products with established quality and safety standards, helps to minimize these risks, thus contributing to the safety of the domestic market. When consumers are confident in product safety and quality, they are more likely to engage in economic activity, resulting in a dynamic and stable market.